The Effect of Number Media Games on the Counting Ability of 5-6 Year Old Children at Dharma Wanita Kindergarten, Kedurang District - Iswi, Rinzi; Ardina, Mona; Wembrayarli (Journal of Early Childhood Development and Education, 2024)
The purpose of this study was to find out the effect of the number block media on the numeracy ability of group B TK Dharma Wanita Kedurang District. This study used a quantitative approach with the type of research True experimental with Pretest-posttest Control Group Design. The population in this study was  26 children of group B. Determination of the sample in this study using saturated sampling. The data collected by using observation and test methods. Data analysis techniques to test in this study using the t-test. Based on the analysis by using a t-test, the t count was (4,005) while the t table was (2.056), which means t count > t table. So based on these results, it concluded that HO can't be accepted and Ha is accepted. Thus, it can be concluded that there is a significant effect of numbers media on the numeracy ability of group B children in Dharma Wanita Kindergarten, Kedurang District. It suggested that the teachers could follow up on the use of numbers media on early childhood numeracy ability and teachers should make other games that can also determine children's numeracy abilities.